Μελέτη διαφορικών ενεργών διατομών της ελαστικής σκέδασης 6Li(d,d0) για αναλυτικούς σκοπούς - Ντέμου, Ελένη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2017)
In the present work differential crosssection values for deuteron elastic scattering from 6Li, 6Li(d,d0)6Li, were determined in the energy range Ed;lab = 940 2000 keV in steps of 20 30 keV and for five backscattering angles 125 , 140 , 150 , 160 , 170 suitable for Elastic Backscattering Spectroscopy. The experiment was carried out at the 5.5 MV Tandem Accelerator of the Institute of Nuclear and Particle Physics (INPP), National Centre of Scientific Research (NCSR) ‘‘Demokritos", Athens, Greece. The target used for the crosssection measurements was made at N.C.S.R. "Demokritos" using the evaporation technique. At first, a small quantity of highpurity, isotopically enriched 6LiF powder (97% in 6Li) was evaporated on selfsupporting carbon foils and an ultrathin Au layer was subsequently evaporated on top for normalization purposes. The detection system consisted of five Si surface barrier detectors (SSB) which were mounted at the laboratory scattering angles of 125 , 140 , 150 , 160 , and 170 , along with the corresponding electronics. The spectra from all five detectors were simultaneously recorded for each deuteron beam energy. The determination of the differential crosssection values for 6Li was carried out using the relative measurement technique making use of the differential crosssection values of gold that follow the Rutherford formula. Moreover, the enrichment of the target had to be determined. For this purpose, proton EBS spectra from a similarly prepared thin natLiF target were used at Ep;lab = 1600 keV and 1700 keV in five scattering angles (125 , 140 , 150 , 160 , 170 ) along with the deuteron spectra. Finally, the differential crosssection values of the present work for the elastic scattering process 6Li(d; d0)6Li and for the five backscattering angles (125 , 140 , 150 , 160 , 170 ) are presented both in tabulated and graphical form. The strong deviations from Rutherford formula and the angular ditribution are both discussed.